PELATIHAN DESAIN POSTER DENGAN APLIKASI CANVA DI MTS AL HIDAYAH - Dani; A. Nurul Anwar (Abdi Jurnal Publikasi, 2024)
The lack of understanding of students at Mts Al Hidayah is one of the reasons for the lack of results in poster competitions which are usually held at Mts level, and the lack of student creativity in making school assignments which are usually done by students in general. Therefore, we as the Pamulang University PKM Team held poster design skills training using the Canva application as one of the media which is very helpful in the field of posters and making school assignments. direct practice, previously the Pkm team provided material in lectures and direct practice. Meanwhile, after the pkm team held poster design training using the Canva application, all students who took part made progress in understanding the material with the results of the assignments that the pkm team had given. the pkm team concluded that with this poster design training, Mts Al Hidayang students were able to understand and even about the application of poster design and they can also implement it in various fields. And the hope of the Pkm team in the future is that students can have even better abilities if they already have a basic knowledge.